Formation and inhibition of heterocyclic amines in meat products - Puangsombat, Kanithaporn (Kansas State University, 2010)
Heterocyclic amines (HCAs) are produced in meats cooked at high temperature, which are potent mutagens and a risk factor for human cancers. Occurrence of HCAs in ready-to-eat (RTE) meat products and cooked meat products based on prevalence of various cooking methods that are preferred among U.S. meat consumers were investigated. The primary HCAs detected in samples were PhIP (2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine), MeIQx (2-amino-3,8-dimethylimidazo [4,5-f]quinoxaline), and DiMeIQx (2-amino-3,4,8-trimethyl-imidazo [4,5-f]quinoxaline). RTE meat products were ranked in the following order of increasing total HCA content: pepperoni (0.05 ng/g) < hot dogs and deli meat products (0.5 ng/g) < fully cooked bacon (1.1 ng/) < rotisserie chicken meat (1.9 ng/g) < rotisserie chicken skin (16.3 ng/g). In cooked meat products, high levels of total HCAs were found in fried pork (13.91 ng/g), fried fish (14.91 ng/g), and fried bacon (17.91 ng/g). Inhibition of HCAs by rosemary extracts, which were extracted with different solvents, were evaluated in cooked beef patties. Five rosemary extracts were 100W (100% water), 10E (10% ethanol), 20E (20% ethanol), 30E (30% ethanol), and 40E (40% ethanol). Rosemary extract 20E containing a mixture of rosmarinic acid (27.3 mg/g), carnosol (72.9 mg/g), and carnosic acid (4.2 mg/g) showed the greatest inhibition of MeIQx (up to 91.7%) and PhIP (up to 85.3%). The effect of enhancement and marination on HCA formation in meat products was investigated. The addition of salt and phosphate greatly improved the water-holding capacity and decreased HCA formation (up to 58%) in enhanced fresh meat products. An greater reduction of HCAs (up to 79%) was found in marinated fresh meat; the enhancement solution for this meat contained ingredients that exhibited good antioxidant properties.
Keywords: heterocyclic amines; carcinogen; meat; cooking; formation; inhibition; Agriculture, Food Science and Technology (0359)